AN ANALYSIS OF FIGURATIVE LANGAUGE IN THE NOVEL THERE YOU’LL FIND BY JENNY B. JONES - Saum Maria; bejo Sutrisno (Journal of English Language and Literature (JELL), 2016)
The objectives of this research are (1) to find out what kinds of figurative language used in the novel, (2) to find out what figurative language the novel used widely and (3) to find out what figurative language used least. The data the researcher analyzed is all sentences which consist of figurative language mentioned in the source of theories in the chapter two of this term paper. The used data source is the novel entitled There you’ll Find Me by Jenny B. Jones. The researcher analyzed the novel by underlining every single sentence found containing figurative language. Then list them in a table and percentage their each types. The researcher found there are 11 figurative languages or, in other words, the novel used all kinds of figure of speech mentioned according to the expert’s theories in total use of 479 figurative languages. The percentage table shows the result that the use of metaphor is 35 or 7.3%, simile 70 or 14.6%, personification 81 or 16.9%, apostrophe 15 or 3.1%, overstatement (hyperbole) 162 or 33.8%, understatement (litotes) 23 or 4.8%, metonymy 20 or 4.2%, synecdoche 18 or 3.8%, transferred epithet 37 or 7.7%, paradox 15 or 3.1%, and pun 3 or 0.6%. According to the result, overstatement (hyperbole) is the most widely used figure of speech, and pun is the least one. The result of this research can give the readers about kinds of figurative languages; perhaps, they found some are new for them. Hopefully, the author of the novel keeps going creating such an interesting yet meaningful story through many other kinds of figurative language.